Analysis of the Influence of Regional Original Income, Balance Fund, Economic Growth, and Inflation on Capital Expenditure in Malang Regency - Dharmawan, Jauhar Arief; Marseto, Marseto (International Journal of Economics, Business and Innovation Research, 2024)
The existence of regional autonomy and fiscal decentralization can be expected for local governments to have greater independence in regional finance and provide a higher proportion of capital expenditure budget allocation to improve community welfare and equitable development. This study was conducted to see how much the influence of Regional Original Revenue, Balance Fund, Economic Growth, and Inflation on Capital Expenditure in Malang Regency during 2009-2023. The results of this study explain that partially Regional Original Revenue has a positive and significant influence on Capital Expenditure. The Balance Fund has a negative and insignificant influence on Capital Expenditure. Economic growth has a positive and insignificant influence on capital expenditure. And inflation has a negative and insignificant influence on Capital Expenditure. Meanwhile, simultaneously the variables of Regional Original Revenue, Balance Fund, Economic Growth, and Inflation have a significant influence on Capital Expenditure in Malang Regency.